Laser Scanning and Photogrammetry for Graphic Analysis and Heritage Documentation: The Lopera Tower, a 14th-Century Castilian Fortress - Juan Francisco Molina Rozalem; Jesús Rodríguez Medina; Ignacio Acosta (Applied Sciences)
Spain is among the European countries with the greatest number of preserved castles and defensive structures—some estimates place the total at around 10,000, the majority of which date back to the medieval period. Yet, surprisingly, many of these fortifications remain uncatalogued and in an advanced state of ruin. This study focuses on a small fortress that has been overlooked by historiography and neglected by public authorities, yet which still stands after seven centuries: the Tower of Lopera, a castle belonging to the so-called Banda Morisca (the frontier of Al-Andalus in the 14th century). Using a combination of digital documentation techniques—namely, portable laser scanning, photogrammetry (via drone and camera), and digital image processing software—we have been able to digitize, geometrize, and document both the surviving architectural remains and their immediate physical environment. Rather than pursuing the latest technological innovations, this methodology prioritizes practical and realistic solutions based on the resources typically available to cultural heritage administrations. Our work serves two main objectives: to demonstrate the viability of applying such tools to this typology of architectural heritage and to conduct a detailed graphic and geometric analysis of the structure. Given the abundance of similar abandoned fortresses in Spain, the findings presented here could inform future heritage documentation strategies on a broader, potentially national, scale.